Pelatihan Robot Line Follower untuk meningkatkan minat Pelajar SMA terhadap Teknik Mesin - Dedi Suryadi; Zuliantoni Zuliantoni; Tessa Zulenia Fitri; Sri Astuti; Arie Vatresia (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2024)
Majoring in mechanical engineering can be a very promising option for high school students who want to pursue a career in robotics technology. The development of the robotics industry continues to experience rapid growth as more and more manufacturers automate their facilities every year. Robotics learning provides students with combined material from various fields of science, especially mechanics, electronics, and computers. The rapid development of technology allows the development of artificial intelligence systems and automation in various fields. One of them is the field of robotics. This training uses a Line Follower robot because the manufacturing process is considered not too difficult, it is hoped that students can learn the manufacturing techniques quickly. This Community Service activity aims to improve the quality of knowledge and skills of high school students. They will be guided in training to make a Line Follower robot, a type of mobile robot that is tasked with detecting and following the guide lines available on the track. From this activity, the results of pre-test and post-test data from the participants, training modules, line-follower robots were obtained. The data obtained from the test results showed that there was an increase from 35.4% to 55.7% in basic knowledge and an increase of 56.6% in interest in robotics in students of SMAN 8 Kota Bengkulu after they received line follower robot training. In the results of community service, enthusiasm and high desire from students in deepening their knowledge of Line Follower robots were seen